Exercise Intensity and Brain Plasticity: What’s the Difference of Brain Structural and Functional Plasticity Characteristics Between Elite Aerobic and Anaerobic Athletes? - Zhang, Keying; Jan, Yih-Kuen; Liu, Yu; Zhao, Tao; Zhang, Lingtao; Liu, Ruidong; Liu, Jianxiu; Cao, Chunmei (Frontiers in Human Neuroscience, 2022)
This study investigated the differences in morphometry and functional plasticity characteristics of the brain after long-term training with different intensities. Results showed that aerobic group demonstrated higher gray matter volume in the cerebellum and temporal lobe, while anaerobic group demonstrated higher gray matter volume in the region of basal ganglia. In addition, aerobic group also showed significantly higher fALFF and DC in motor area of frontal lobe and parietal lobe, and the frontal gyrus, respectively. At the same time, anaerobic group demonstrated higher fALFF and DC in the cerebellum posterior lobe. (FWE corrected, p < 0.01). These findings may further prove that different brain activation modes respond to different intensities of physical activity and may help to reveal the neural mechanisms that can classify athletes from different intensity sports.